2019
DOI: 10.1159/000499717
|View full text |Cite
|
Sign up to set email alerts
|

SCCA-IgM as a Potential Biomarker of Non-Alcoholic Fatty Liver Disease in Patients with Obesity, Prediabetes and Diabetes Undergoing Sleeve Gastrectomy

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) has a high prevalence in obesity and its presence should be screened. Laparoscopic sleeve gastrectomy (LSG) is an effective treatment for obesity, but its effects on NAFLD are still to be firmly established. The diagnosis of non-alcoholic steatohepatitis (NASH) is currently performed by liver biopsy, a costly and invasive procedure. Squamous cell carcinoma antigen-IgM (SCCA-IgM) is a biomarker of viral hepatitis to hepatocellular carcinoma development and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(76 reference statements)
0
2
0
Order By: Relevance
“… 16 , 30 NAFLD has mutual influence with GDM 7 and a study among non-obese Chinese population without NAFLD at baseline reported the increase in the ALT/AST was associated with the risk of new-onset NAFLD. 17 Bettini et al 31 found ALT/AST decreased in patients with obesity after laparoscopic sleeve gastrectomy and was correlated with BMI and insulin reduction. Since insulin resistance, NAFLD and BMI are all closely related to the development of GDM, it is reasonable that ALT/AST presented close association with GDM and can be an independent risk factor of GDM.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 30 NAFLD has mutual influence with GDM 7 and a study among non-obese Chinese population without NAFLD at baseline reported the increase in the ALT/AST was associated with the risk of new-onset NAFLD. 17 Bettini et al 31 found ALT/AST decreased in patients with obesity after laparoscopic sleeve gastrectomy and was correlated with BMI and insulin reduction. Since insulin resistance, NAFLD and BMI are all closely related to the development of GDM, it is reasonable that ALT/AST presented close association with GDM and can be an independent risk factor of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, liver biopsy is not the ideal method for repeated assessments of disease progression, and new non-invasive procedures are needed. Several scores and indexes have been validated to detect advanced hepatic fibrosis in patients with NAFLD, such as the alanine aminotransferase (ALT)/aspartate aminotransferase (AST) ratio, the AST-to-platelet ratio index (APRI), and the Fibrosis-4 Index (FIB-4) [ 27 , 28 , 29 , 30 ], and innovative biomarkers have been proposed in patients with obesity [ 31 ]. Moreover, imaging methods have been developed, such as transient elastography (TE), FibroScan ® , and shear wave elastography (SWE).…”
Section: Introductionmentioning
confidence: 99%